2015
DOI: 10.17554/j.issn.2224-3992.2015.04.566
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum anti-Helicobacter pylori IgG Levels is a Predictor of Successful Eradication Therapy

Abstract: habits, prior PPI intake, kind of PPI, serum IgG value and degree of atrophy. Univariate analysis showed that high serum IgG significantly predicts successful eradication (odds ratio (OR) 2.583, 95% confidence interval (CI) 1. 285-5.191, p=0.008). The eradication rate was 77% (43/56) in the ≥45 U/mL group and 56% (73/130) in the <45 U/ mL group, and significance was confirmed by multivariate analysis (OR 2.626, 95% CI 1. 269-5.436, p=0.009). Multivariate analysis showed a trend that advanced age (≥70 year-old)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Shinozaki et al reported that "high serum anti-HPIgG levels significantly predicts successful eradication of oral antibiotic therapy (OR: 2.583; 95% CI: 1.285-5.191; p = 0.008) due to the co-operative effect of antibiotic susceptibility and high humoral immunity" [33]. Our study showed that the eradication rate of ILTHPI was not influenced by serum anti-HPIgG.…”
Section: Discussionsupporting
confidence: 43%
“…Shinozaki et al reported that "high serum anti-HPIgG levels significantly predicts successful eradication of oral antibiotic therapy (OR: 2.583; 95% CI: 1.285-5.191; p = 0.008) due to the co-operative effect of antibiotic susceptibility and high humoral immunity" [33]. Our study showed that the eradication rate of ILTHPI was not influenced by serum anti-HPIgG.…”
Section: Discussionsupporting
confidence: 43%